EXTRALINGUISTIC FEATURES OF LAWYERS' WRITTEN SPEECH (American Journal of Interdisciplinary Research and Development, 2025)
Legal writing is a complex form of communication. Just as syntax, semantics, and legal terminology are important, extralinguistic features - that is, the state of communication, social roles, institutional context, and cultural norms - play an important role in the structure and content of documents written by lawyers. This article analyzes the most relevant extralinguistic factors in the written speech of lawyers and examines their influence on content, interpretation, and legal force. The analysis is based on various legal documents: contracts, court decisions, and professional correspondence. The article substantiates the importance of the role of extralinguistic factors in the formation of clear and professional communication in legal texts.